Posisi Tasawuf Teoretis dalam Tinjauan Logika Tafsir Al-Qurâan - Gama, Cipta Bakti (Sekolah Tinggi Filsafat Islam Sadra, 2016)
ThisÂ paperÂ addressesÂ theÂ issueÂ ofÂ howÂ theÂ positionÂ ofÂ theoreticalÂ SufismÂ inÂ the interpretationÂ ofÂ theÂ Qurâan.Â DepartingÂ fromÂ someÂ reasonsÂ forÂ rejectingÂ theÂ validity ofÂ SufisticÂ methodÂ ofÂ QurâanicÂ interpretationÂ (isharÄ«Â method),Â theÂ authorÂ seesÂ the needÂ toÂ explainÂ theÂ natureÂ ofÂ theoreticalÂ SufismÂ andÂ itsÂ positionÂ basedÂ onÂ theÂ logic ofÂ QurâanicÂ exegesis.Â SomeÂ importantÂ pointsÂ whichÂ theÂ authorÂ triesÂ toÂ showÂ inÂ this paper are five principles, as follows: First, the theoretical Sufism could be positioned asÂ aÂ sourceÂ ofÂ interpretationÂ ofÂ theÂ Qurâan.Â Second,Â shuhÅ«dÂ âirfÄnÄ«Â whichÂ isÂ theÂ main foundation of theoretical Sufism could be positioned as a source of interpretation of the Qurâan, in the context of the disclosure of meaning, not in the explanation of it. Third, theoretical Sufism might be used as a source or indicator to determine a position in the interpretation of the Qurâan. Fourth, every hypothetical (zhannÄ«) proposition in the QurâÄnic interpretation must not conflict with the certaint (qaá¹âÄ«) rational proposition in the theoretical Sufism. Fifth, Sufistic interpretation of the Qurâan is a particular form of a set of method of Qurâanic interpretation, which can be combined with the other methods, to achieve an eclectic and holistic interpretation of the Qurâan. The author also gives an example as the application of those five principles in the interpretation of the meaning of khalÄ«fah fÄ« al-ardh in al-Baqarah [2]: 30.